2017
DOI: 10.1038/sc.2017.64
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death after traumatic spinal cord injury—a 70-year British study

Abstract: Leading causes of death after tSCI in persons surviving the first year post injury were respiratory, circulatory, neoplasms and urogenital. Cause-specific mortality rates showed improvement over time for most causes, but were still higher than the general population rates, especially for skin, urinary and respiratory causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 16 publications
2
76
2
3
Order By: Relevance
“…These risk factors are also highly prevalent among people with spinal cord injury (SCI) . Plausible explanations for this heightened cardiovascular risk are autonomic dysfunction, metabolic and body composition changes, and a sedentary lifestyle , which are considered to contribute to CVD now being the leading cause of death also for people with SCI .…”
Section: Introductionmentioning
confidence: 99%
“…These risk factors are also highly prevalent among people with spinal cord injury (SCI) . Plausible explanations for this heightened cardiovascular risk are autonomic dysfunction, metabolic and body composition changes, and a sedentary lifestyle , which are considered to contribute to CVD now being the leading cause of death also for people with SCI .…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular diseases, suicide, and systemic infections are the leading causes of death in the present study population when excluding accident and nervous systemrelated ICD codes. In comparison with previous studies, some discrepancies in leading causes of death can be noted; for example, Savic et al [13] reported respiratory diseases (including infections), circulatory diseases and neoplasms as the leading causes of mortality for individuals who survived at least 1 year post-injury. Additionally, in terms of direction and magnitude of the effect, differences exist between country-level comparisons of cause-specific SMRs.…”
Section: Discussionmentioning
confidence: 60%
“…A categorical variable was created to group causes of death into 6 broad categories based on expert opinion, previous literature [13], data availability, as well as identifying meaningful groups for targeted prevention. These groups include respiratory diseases (ICD-10 codes = J30-J99 -excluding respiratory infections); cardiovascular disease (I00-I99); neoplasms (C00-D49); infections (including respiratory and urinary tract infections (UTIs): A00-B99, J00-J22, N390-392); accidents (S00-Y99, excluding X60-X84); and all other causes of mortality.…”
Section: Causes Of Deathmentioning
confidence: 99%
“…However, despite the advances made in the last decades in the management of urinary control dysfunction of SCI subjects, upper and lower urinary tract complications are still common and represent one of the leading cause of re‐hospitalization after SCI . Furthermore, although the rate of mortality due to renal failure progressively decreased along time, urogenital complications still represent the cause of death in about 11% of subjects with SCI . Therefore, the major effort of the research is concentrated on the treatment of neurogenic bladder dysfunction, aiming at avoiding urinary tract problems.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Furthermore, although the rate of mortality due to renal failure progressively decreased along time, urogenital complications still represent the cause of death in about 11% of subjects with SCI. 8 Therefore, the major effort of the research is concentrated on the treatment of neurogenic bladder dysfunction, aiming at avoiding urinary tract problems.…”
Section: Introductionmentioning
confidence: 99%